The Duration of Patent Examination at the European Patent Office - Harhoff, Dietmar; Wagner, Stefan (Management Science, 2009)
We analyze the duration and outcomes of patent examination at the European Patent Office utilizing an unusually rich data set covering a random sample of 215,265 applications filed between 1982 and 1998. In our empirical analysis, we distinguish between three groups of determinants: applicant characteristics, indicators of patent quality and value, and determinants that affect the complexity of the examination task. The results from an accelerated failure time model indicate that more controversial claims lead to slower grants but faster withdrawals, whereas well-documented applications are approved faster and withdrawn more slowly. We find strong evidence that applicants accelerate grant proceedings for their most valuable patents, but that they also prolong the battle for such patents if a withdrawal or refusal is imminent. This paper develops implications of these results for managerial decision making in research and development and innovation management.